Optimization On Acipolysi Reaction Of Palm Stearin And Oleic Acid By Dual Lipase System And Its Physicochemical Characteristics - Nur Atikah Binti Muhammad
Acidolysis reaction makes the acyl group specificallyt o be incorporated into the triacylglycerol of palm stearin. The acidolysis reaction was optimized to measure its optimum condition of reaction and the effect of dual lipase system used in this reaction through its interesterification degree (ID). The final product is expected to have healthier fatty acid composition and characteristics compare to palm stearin. In this study, acidolysis reaction was catalyzed by lipase Amano AK and immobilized lipase Theimomycesla~~uginoses(TILM ). All four parameters affecting the reaction-enzyme ratio (wlw), enzyme load (%), reaction time (h) and substrate molar ratio (wlw), were optimizedvia Response Surface Methodology (RSM) using Central Composite Rotatable Design (CCRD). The responses measured were percentage of free fatty acid (FFA) and fatty acid compostion (FAC) of oleic acid. The target was to have the minimum FFA percentage and maximum FAC of oleic acid in the final product. The physicochemical analysis of triacylglycerol (TAG) composition, FAC percentage and its slip melting point (SMP) profile were conducted to the finished product to compare with the palm stearin. From the RSM, the optimum condition obtained were 3 hours of time reaction, 5:5 (w/w)of enzyme ratio, 1:3 (w1w)of substrate molar ratio and 10% (w/w) enzyme load. Among these four factors, the substrate molar ratio was found to have a significant effect (p<0.0001) towards the percentage of FFA while in contrast towards percentage of FAC of oleic acid, the enzyme ratio, enzyme load, and reaction time had a significant effect (p<O.OOOl).The synergistic effect between the two lipases with ratio 5:5 gives average interesterification degree (ID) of 0.73. Slip melting point for purified modified palm stearin (PMPS) was 46.13"C. TAG composition of oleic-oleic-oleic(000) and palmitic-oleic-oleic (P0O)as well as percentage of FAC of oleic acid increased in their percentage after the reaction. These conclude that the model given by RSM can be implied to predict the responses as well as interactions between the parameters and the finished product, PMPShave a lower melting point and healthier fatty acid composition as compared to palm stearin.